Under Construction: Open Access und Forschungsdaten in Bauingenieurwesen, Architektur und Urbanistik - Wermbter, Katja; Elsner, Carsten (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2022)
The eight „fields of action“ defined within the framework of the specialized information service (FID) BAUdigital address researchers from the disciplines of civil engineering, architecture, and urban studies in an interdisciplinary manner. In „field of action 8“, open access and publication services, specific information and consulting services on open access are developed for this community. Previous studies and expert discussions have already shown that the targeted disciplines differ in their publication cultures. A more in-depth analysis of the specifics of the disciplines seemed necessary and was achieved primarily through an online survey of the FID community. This paper presents the results of the online survey on “Open Access and Research Data Management”, which was conducted in spring 2021. It shows that, for various reasons, open access is not (yet) the preferred form of publication in the subjects mentioned. Self-archiving and the publication of research data also haven’t played a significant role among the surveyed representatives of the disciplines. At the same time, it was emphasized that active support and advice in the publication process, as well as financial support for open access publications, might create the necessary incentives to change this.
Keywords: Open Access; Research Data; Specialized Information Services; Civil Engineering; Architecture; Urbanism; Survey